Ten challenges for the future of pedometrics - Wadoux, Alexandre M.J.-C.; Heuvelink, Gerard B.M.; Lark, R. Murray; Lagacherie, Philippe; Bouma, Johan; Mulder, Vera L.; Libohova, Zamir; Yang, Lin; McBratney, Alex B. (Geoderma, 2021)
•Community-based research effort.•Define ten challenging and unsolved pedometrics questions.•Review and proposed agenda for each challenge.•Guide for future pedometrics research.•Foster collaboration among soil scientists to solve the challenges. Pedometrics, the application of mathematical and statistical methods to the study of the distribution and genesis of soils, has broadened its scope over the past two decades. The primary focus of pedometricians has traditionally been on spatial and spatio-temporal soil inventories with numerical soil classification, geostatistical modelling of spatial variation and mapping. The rapid development of remote and proximal soil sensing as well as data-driven statistical modelling techniques have had a major impact on pedometrics over the past decades. During this time, a general demand for quantitative digital soil information for environmental modelling and management has compelled pedometricians to address other soil-related questions from a quantitative point of view: soil genesis and utility and quality of soil. While scientific progress is largely an autonomous process that is difficult to steer, research efforts could benefit from an agenda with pressing pedometric research topics. This paper defines and discusses ten recent or longstanding pedometrics challenges, with the attempt to identify knowledge gaps and suggest new concepts and methods to overcome them. The ten challenges were selected through a collaborative effort and may serve as a guidance for future pedometrics research and to foster collaboration among soil scientists. The challenges discussed in this paper are also indicators of the current understanding and state of knowledge from which progress can be measured in the future.